Life cycle assessment for municipal solid waste management scenarios in Humaitá, state of Amazonas: the impact of including collection in indigenous areas - Hanada Menichelli, Beatriz; Otávio Souza de Oliveira, Benone; Araújo de Medeiros, Gerson (Seven Editora, 2023)
In the Amazon, around 80% of the municipalities dispose of their waste in open-air dumps, challenging government agencies to find alternatives for its management. In this context, the Life Cycle Assessment (LCA) methodology has been used to analyze the environmental impact of municipal solid waste (MSW) management system scenarios. The objective of this chapter was to analyze municipal solid waste management scenarios, based on the LCA methodology, in the municipality of Humaitá, state of Amazonas, including the collection of waste from indigenous communities. This study included secondary data from articles published by a research partnership between the São Paulo State University (Unesp) and the Federal University of Amazonas (UFAM). The LCA followed the model proposed by ISO 14040 and 14044 and was performed using the Simapro software. The environmental impact category assessed corresponded to greenhouse gas (GHG) emissions, expressed in kgCO2eq. Three scenarios were evaluated: a) Base scenario (CB): which corresponded to the collection of waste from the urban area of Humaitá, transport, and disposal in a sanitary landfill; b) Scenario 1 (C1): which corresponded to CB with the inclusion of the collection of waste generated in indigenous areas; c) Scenario 2 (C2): corresponded to C1, excluding organic waste, which would be destined for composting. The analysis of the inventories of each scenario led to the conclusion that including the collection of solid waste from indigenous reserves would increase GHG emissions by 4%.DOI: https://doi.org/10.56238/devopinterscie-131